Developing partnership with patients and carers: A need of the time for mental health service delivery - Afzal Javed, (Journal of the Pakistan Medical Association, 2024)
Contemporary practice of psychiatry is witnessing a radicle shift in the care of mentally ill. As compared to the 20th century, we are now moving towards community psychiatry and large mental hospitals and asylums are closing with a shift to manage these patients closer to their homes. Following these changes in mental health care, current literature provides growing evidence for developing partnership with patients, carers and family members in the delivery of mental health services. While this approach is appreciated for improving the quality of life of patients, there has also been some concerns about increasing burden of carers and families when they have limited resources and support to face the challenges in dealing with the management of their patients.1 Treatment and management of mental health problems are complex and needs a wider recognition for having patients and care-givers involvement in the treatment processes. Patients with mental health problems unfortunately suffer from a wide range of psychosocial adversities and require engagement leading to more empowerment in decision making processes. Furthermore, quality of health services can be measured by the experiences of patients and their families. Their viewpoints can reflect their happiness as well as the effectiveness of the services that could be based on their knowledge and understanding of their role in the treatment processes. However, in many societies, the nature and role of families are either undermined or not fully understood.2 Families may be considered as a cause for the onset of mental health issues and can be blamed for causing or triggering the illnesses. Similarly, the clinicians are given the full authority to decide about the treatment choices and preferred possibilities. Their role may be acknowledged as “the ultimate expert” who can decide in a final way and patients or families may have limited opinions in such decisions. Professionals may also consider confidentiality issues as a primary reason for not sharing information and taking relatives or family members on board, so they are frequently excluded from the decision-making processes. Apart from confidentiality reasons, clinicians may not have sufficient training and skills to deal with families and patients in terms of supporting and dealing with their concerns.3 Continued...